Treatment and management of 1,5 cm diameter appendiceal neuroendocrine tumors: a gray zone - Montali, Filippo; D'Agostino, Filippo; Annicchiarico, Alfredo; Rollo, Alessio; Virgilio, Edoardo; Costi, Renato (Acta Biomedica Atenei Parmensis, 2024)
Appendiceal neuroendocrine tumours are rare and often diagnosed as incidentalomas after an appendectomy for acute appendicitis. Appendiceal tumours can cause appendiceal torsion, eventually resulting in acute appendicitis. In the international guidelines (NANTS and ENETS), tumour size is the main prognostic factor and is associated with os and lymph node relapse (LNM). Right hemicolectomy for tumours >2cm in diameter and simple appendicectomy for those